Implementasi Model Beyond Centers and Circles Time Dalam Mengembangkan Kreativitas Anak Usia Dini Pada PAUD Kusma Kelurahan Sudiang Raya Kecamatan Biringkanaya Kota Makassar - Nini Pratiwi (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
This research aims to describe the result evaluation of: reducting data, presenting data, conclusion of Beyond Centers and Circles time in PAUD KUSMA. The data were collected through a questionnaire, interviews, and observation. Subject of this research are consits of 13 children and 2 tutor. The data were analized by using the qualitative descriptive. The result of this research is implementation of BCCT model are 1) environment scaffolding, 2) scaffolding before playing, 3) scaffolding over playing, 4) scaffolding after playing. Conclusion of this research are tutor overing condition of children to be circle in the classroom; the children are centered by tutor to introduting the topic of learning; the children begin for play the activity; conclusion; children put toys to the rack.